ORPHAcodes use for the coding of rare diseases: comparison of the accuracy and cross country comparability - Mazzucato, Monica; Pozza, Laura Visonà Dalla; Facchin, Paola; Angin, Cèline; Agius, Francis; Cavero-Carbonell, Clara; Corrochano, Virginia; Hanusova, Katerina; Kirch, Kurt; Lambert, Deborah; Lucano, Caterina; Maiella, Sylvie; et al. (Orphanet journal of rare diseases, 2023)
BACKGROUND: Estimates of rare disease (RD) population impact in terms of number of affected patients and accurate disease definition is hampered by their under-representation in current coding systems. This study tested the use of a specific RD codification system (ORPHAcodes) in five European countries/regions (Czech Republic, Malta, Romania, Spain, Veneto region-Italy) across different data sources over the period January 2019-September 2021. RESULTS: Overall, 3133 ORPHAcodes were used to describe RD diagnoses, mainly corresponding to the disease/subtype of disease aggregation level of the Orphanet classification (82.2%). More than half of the ORPHAcodes (53.6%) described diseases having a very low prevalence (< 1 case per million), and most commonly captured rare developmental defects during embryogenesis (31.3%) and rare neurological diseases (17.6%). ORPHAcodes described disease entities more precisely than corresponding ICD-10 codes in 83.4% of cases. CONCLUSIONS: ORPHAcodes were found to be a versatile resource for the coding of RD, able to assure easiness of use and inter-country comparability across population and hospital databases. Future research on the impact of ORPHAcoding as to the impact of numbers of RD patients with improved coding in health information systems is needed to inform on the real magnitude of this public health issue.
Keywords: Humans; Rare Diseases; databáze faktografické; lidé; Epidemiology; ICD-10; Europe; Databases, Factual; Rare diseases; ORPHAcodes; Hospitals; Public health; Coding; Czech Republic; nemocnice; Orphanet; Česká republika; vzácné nemoci; Diagnoses; Evropa